Are reframing strategies more effective than empathy in processing trauma reports? A pilot study - Leuteritz, Sophie; Böhme, Stephanie; Mühlberger, Andreas; Greve, Werner (Frontiers in Psychology, 2023)
Listening to trauma reports can result in symptoms of secondary traumatization. Especially psychologists in education have to establish strategies to process such events. This explorative study investigated adaptive reframing strategies for future therapists listening to trauma stories in comparison to feeling empathetically into the client. In a mixed design, 42 postgraduate psychology students were randomly instructed to objectively distance themselves, reappraise, or feel empathetic while watching a video of a presumed trauma patient reporting a single violent act. An overall ANOVA did notn’t reveal a difference between the reframing groups and the empathy group (between subjects manipulated) in their skin conductance level and heartrate variability during the video as well as their change of state-depression and state-anxiety over the three measurements (before the video, after the video, two days later). Nevertheless, an explorative t-test showed a significant weaker rise of state-depression and state-anxiety from before to after the video in the reframing groups compared to the empathy group. This supports the suggestion that reframing strategies can be discussed as a protective factor against health issues like secondary traumatization in therapists and should be examined in further studies in more detail.